Revelation of enzyme activity of mutant pyrazinamidases from Mycobacterium tuberculosis upon binding with various metals using quantum mechanical approach. (December 2019) - Rasool, Nouman; Husssain, Waqar; Khan, Yaser Daanial
Graphical abstract: Highlights: Mutagenicity and metal substitution in PZase weakens the binding of PZA with PZase The present study aims at the quantum mechanistic analysis of mutant-metal substituted PZase complexes All the targeted mutations casts derogatory effect on the activity of PZase The substitution of iron with cobalt enhances the enzymatic activity of both wild type and mutant PZase Abstract: Pyrazinamide (PZA) is one of the most potent bacteriostatic drug against tuberculosis, a deadliest disease with high mortality and morbidity rate. PZA metabolizes into its active form pyrazinoic acid (POA) with the help of a metalloenzyme, pyrazinamidase (PZase). Mutagenicity and metal substitution in PZase weakens the binding of PZA with PZase and increases the drug resistance in Mycobacterium tuberculosis . The present study aims at the quantum mechanistic analysis of mutant-metal substituted PZase complexes by studying the mechanics of metals and PZA binding at MCS and catalytic site, respectively. A total of 66 complexes are scrutinised in this study to elucidate the effect of mutations on the enzymatic function of PZase. Among the 10 mutations considered in this study, 7 different mutations i.e. Asp49 → Asn, His51 → Arg, Gly78 → Cys, Asp12 → Gly, Asp12 → Ala, Thr135 → Pro and Asp136 → Gly cause a detrimental effect on the activity of PZase. In addition to this, the substitution of iron with cobalt enhances the enzymatic activity of both wild type and mutant PZase while zinc, magnesium and copper reduce it. Based on these results, it is concluded that upon substitution of iron with zinc, magnesium and copper, PZase cannot function properly. Due to mutations, the reactivity of the drug also reduces as its binding with PZase weakens and this phenomenon enhances the resistance of Mycobacterium tuberculosis against drug.